Perlindungan Hak Konstitusional Warga Negara melalui Penguatan Mekanisme Judicial Review dalam Negara Hukum Demokratis Indonesia Modern Berkelanjutan - Pandu Widodo; Lukman Hadi; Dina Mariana (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2025)
The protection of citizens' constitutional rights is a fundamental element in Indonesia's democratic rule of law. The Constitutional Court plays a strategic role through its judicial review authority, serving as the primary instrument for upholding constitutional supremacy and controlling state power. This study aims to analyze the effectiveness of the judicial review mechanism in protecting citizens' constitutional rights and formulate a direction for strengthening this mechanism in the context of modern Indonesia, which is oriented towards the sustainability of democracy and constitutionalism. This study uses a normative juridical approach, analyzing legislation, Constitutional Court decisions, and constitutional law doctrine. Data are analyzed systematically, logically, and prescriptively to identify gaps between normative guarantees of constitutional rights and their protection in practice. The results show that judicial review has functioned as a corrective mechanism for laws that conflict with the constitution and as a means of strengthening the principle of checks and balances. However, the protection of constitutional rights through this mechanism remains limited because the scope of the Constitutional Court's authority does not yet extend to rights violations resulting from concrete actions by state institutions. In addition, the dynamics of legislative politics and relations between state institutions influence the consistency of constitutional rights protection. This study concludes that strengthening the judicial review mechanism through expanding authority, increasing institutional independence, and integrating the perspective of the sustainability of the rights of future generations is an urgent need to ensure effective protection of constitutional rights in a democratic state under the rule of law in Indonesia.